1999
DOI: 10.1093/oxfordjournals.aje.a009740
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Drug Use Reporting in a High-Risk Community Sample: A Comparison of Cocaine and Heroin Survey Reports with Hair Tests

Abstract: Hair specimens were collected from 322 subjects and analyzed as part of an experimental study administering household surveys during 1997 to a high-risk community sample of adults from Chicago, Illinois. Toxicologic results were compared with survey responses about recent and lifetime drug use. About 35% of the sample tested positive for cocaine, and 4% tested positive for heroin. Sample prevalence estimates of cocaine use based on toxicologic results were nearly five times the survey-based estimates of past m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(75 citation statements)
references
References 20 publications
3
68
0
4
Order By: Relevance
“…[1][2][3][4][5] Of particular importance for researchers on health disparities in substance abuse problems and treatment is the likely possibility that reporting validity in surveys often varies by race/ethnicity. Thus far, the evidence for race/ethnicity variation in substance abuse reporting validity has been suggestive but not conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Of particular importance for researchers on health disparities in substance abuse problems and treatment is the likely possibility that reporting validity in surveys often varies by race/ethnicity. Thus far, the evidence for race/ethnicity variation in substance abuse reporting validity has been suggestive but not conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…(2001) detectaron, en una muestra de pacientes dependientes de opiáceos, que el 72% de los pacientes seguían vinculados al año de seguimiento ambulatorio. Existen otros estudios que objetivan que el tipo de sustancia consumida parece no estar relacionado con la probabilidad de recaída en su consumo (Fendrich et al, 1999;Maddux et al, 1986;Murphy et al, 2010).…”
Section: Discussionunclassified
“…Además los pacientes con pobre motivación hacia el tratamiento y con escasa implicación familiar tienen mayor riesgo de recaída (Goeb et al, 2000;O'Brien y McLellan, 1996). Existe controversia respecto a qué tipo de sustancia, legal o ilegal, se asocia a mayor probabilidad de recaída (Fendrich, Johnson, Sudman, Wislar y Spiehler, 1999;Fischer et al, 2002;Maddux y Desmond, 1986;Murphy, Hser, Huang, Brecht y Herbeck, 2010). Tampoco hay acuerdo sobre las variables sociodemográficas (edad o género) (Goeb et al, 2000;Gottheil, Thornton, Skoloda, y Alterman, 1982;Swett et al, 1989;Xie et al, 2005) o los factores de personalidad (Cervera, Valderrama, Bolinches y Martínez, 1999;McMahon y Enders, 2009;Rubio, León, Pascual y Santo-Domingo, 1998;Rubio et al, 2007).…”
unclassified
“…Comparisons using these methods within NSDUH have shown that they reduce reporting bias (Gfroerer, Eyerman, & Chromy, 2002). Various procedures have been used to validate self-report data, such as biological specimens (e.g., urine, hair, saliva), proxy reports (e.g., family member, peer), and repeated measures (e.g., recanting) (Fendrich, Johnson, Sudman, Wislar, & Spiehler, 1999). However, these procedures often are impractical or too costly for general population epidemiological studies (SRNT Subcommittee on Biochemical Verification, 2002).…”
Section: B34 Validity Of Self-reported Substance Usementioning
confidence: 99%